BRIDGING LEGACY SYSTEMS WITH MODERN PLATFORMS: A SCALABLE APPROACH - Dilipkumar Devarahosahalli Jayaram (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores comprehensive strategies for integrating legacy systems with modern platforms while maintaining operational efficiency and minimizing disruption. The article examines the challenges organizations face in modernizing their technology infrastructure, focusing on the balance between preserving critical legacy investments and adopting contemporary solutions. Through analysis of implementation patterns across various industries, the article presents a framework for successful integration, highlighting the importance of modular architectures, security considerations, and systematic approaches to modernization. The article particularly emphasizes ServiceNow integration patterns and mobility solutions, providing detailed insights into performance optimization, security implementations, and best practices for sustainable digital transformation. The article demonstrates that organizations adopting structured integration approaches achieve significantly better outcomes in terms of system reliability, operational efficiency, and cost management.